2019
DOI: 10.1002/nvsm.1663
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the predictors of young consumers' sustainable consumption intention

Abstract: Sustainable consumption refers to consumers' socially and environmentally responsible consumption practices. The present study is the first to investigate possible individual, behavioural, and situational factors that predict sustainable consumption intention among young consumers in India. A survey was carried out on 325 young consumers. Structural equation modelling was applied to check the extent to which the considered variables predicted sustainable consumption. The results determined drive for environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 76 publications
1
23
0
2
Order By: Relevance
“…In terms of sustainable consumption, social normative influences were already the subject of research regarding food choice (Chekima, Chekima, & Chekima, 2019; Dowd & Burke, 2013; Zhou, Thøgersen, Ruan, & Huang, 2013), purchase of everyday necessities (Demarque et al, 2015; Minton & Rose, 1997; Pickett‐Baker & Ozaki, 2008), energy‐efficient household appliances (Nguyen, Lobo, & Greenland, 2016) and clothing (Kim et al, 2012). While numerous studies evidence effects of social normative influences on sustainable consumption practices (e.g., Cheah, Shimul, Liang, & Phau, 2020; Demarque et al, 2015; Dowd & Burke, 2013; Joshi, Sangroya, Srivastava, & Yadav, 2019; Kim et al, 2012; Loschelder, Siepelmeyer, Fischer, & Rubel, 2019; Minton & Rose, 1997), there are instances that evidence none (Chekima et al, 2019; He & Kua, 2013; Zhou et al, 2013), while others report their ambiguous influence—they affect intentions, but not behaviour (Nguyen, Lobo, Nguyen, Phan, & Cao, 2016). More importantly, while it is theoretically implied that social norms function as a catalyst to personal norm formation, which, in turn, represents the primary determinant of pro‐social behaviour (Hopper & Nielsen, 1991), most studies on sustainable consumption do not explicitly investigate this motivational route as well as its relevance for influences of perceived social norms on behavioural intentions.…”
Section: Conceptual Foundationmentioning
confidence: 99%
“…In terms of sustainable consumption, social normative influences were already the subject of research regarding food choice (Chekima, Chekima, & Chekima, 2019; Dowd & Burke, 2013; Zhou, Thøgersen, Ruan, & Huang, 2013), purchase of everyday necessities (Demarque et al, 2015; Minton & Rose, 1997; Pickett‐Baker & Ozaki, 2008), energy‐efficient household appliances (Nguyen, Lobo, & Greenland, 2016) and clothing (Kim et al, 2012). While numerous studies evidence effects of social normative influences on sustainable consumption practices (e.g., Cheah, Shimul, Liang, & Phau, 2020; Demarque et al, 2015; Dowd & Burke, 2013; Joshi, Sangroya, Srivastava, & Yadav, 2019; Kim et al, 2012; Loschelder, Siepelmeyer, Fischer, & Rubel, 2019; Minton & Rose, 1997), there are instances that evidence none (Chekima et al, 2019; He & Kua, 2013; Zhou et al, 2013), while others report their ambiguous influence—they affect intentions, but not behaviour (Nguyen, Lobo, Nguyen, Phan, & Cao, 2016). More importantly, while it is theoretically implied that social norms function as a catalyst to personal norm formation, which, in turn, represents the primary determinant of pro‐social behaviour (Hopper & Nielsen, 1991), most studies on sustainable consumption do not explicitly investigate this motivational route as well as its relevance for influences of perceived social norms on behavioural intentions.…”
Section: Conceptual Foundationmentioning
confidence: 99%
“…Jordan et al (2014) reported a significant mediation of attitudes in the relationship between trait mindfulness and food choice. Joshi et al (2019) reported a significant mediation effect of attitude on the relationship between perceived knowledge and consumption intention. Lau and Hashim (2020) observed that PBC mediated the effect of environmental concern on green intention.…”
Section: Review Of Literaturementioning
confidence: 93%
“…As mentioned above, firstly, CFA was performed with maximum likelihood method to analyze the validity and reliability of the measurement indicators. Each construct was having good internal consistency as composite reliability (CR) varies from 0.76 to 0.92 (see Table 2), which was higher than the suggested value of 0.70 (Hair et al, 2010;Joshi et al, 2019). The convergent validity of latent constructs was analysed using item loadings and average variance extracted (AVE) (Islam et al, 2019).…”
Section: Measurement Modelmentioning
confidence: 99%